Let f : Z + → Z + with conditions f ( x + 1 ) > f ( x ) , f ( f ( x ) ) = 3 x . Find f ( 9 5 5 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, notice that by definition we have: f ( 3 x ) = f ( f ( f ( x ) ) ) = 3 f ( x ) for all positive integers x . Let's call this equation ( 1 ) .
Second, we can show by induction that if a ≥ b with a , b ∈ N , then f ( a ) ≥ f ( b ) + ( a − b ) . Let's call this inequality ( 2 ) .
Now, we must have f ( 1 ) ≥ 1 , and by (ii), f ( f ( 1 ) ) = 3 . Thus, using ( 2 ) with a = f ( 1 ) and b = 1 , we have: 3 = f ( f ( 1 ) ) ≥ f ( 1 ) + ( f ( 1 ) − 1 ) = 2 f ( 1 ) − 1 Thus f ( 1 ) ≤ 2 . However f ( 1 ) cannot equal 1, because if it did, we would have a contradiction: f ( f ( 1 ) ) = f ( 1 ) = 1 , which does not equal 3 ∗ 1 .
Therefore f ( 1 ) = 2 .
Therefore, by equation ( 1 ) , it's easy to show by induction that for any n ∈ N , we have f ( 3 n ) = 2 ∗ 3 n . Therefore, f ( 2 ∗ 3 n ) = f ( f ( 3 n ) ) = 3 n + 1 .
Therefore, f ( 7 2 9 ) = 1 4 5 8 and f ( 1 4 5 8 ) = 2 1 8 7 .
By ( 2 ) with a = 9 5 5 , b = 7 2 9 , we have f ( 9 5 5 ) ≥ f ( 7 2 9 ) + ( 9 5 5 − 7 2 9 ) = 1 4 5 8 + 2 2 6 = 1 6 8 4 .
Again by ( 2 ) with a = 1 4 5 8 , b = 9 5 5 , we have f ( 1 4 5 8 ) ≥ f ( 9 5 5 ) + ( 1 4 5 8 − 9 5 5 ) , so that f ( 9 5 5 ) ≤ 2 1 8 7 + ( 9 5 5 − 1 4 5 8 ) = 1 6 8 4 .
Hence 1 6 8 4 ≤ f ( 9 5 5 ) ≤ 1 6 8 4 . Therefore f ( 9 5 5 ) = 1 6 8 4
One function that works is as follows: if the base-3 expansion of x starts with a 1 , then f ( x ) is the same expansion, with the 1 replaced by a 2 . And if the base-3 expansion of x starts with a 2 , then f ( x ) replaces the 2 with a 1 and adds a 0 on the far right.
This f clearly satisfies the conditions of the problem. I believe it is unique, but the problem doesn't ask us to prove that.
In any case, 9 5 5 's ternary expansion starts with a 1 , since 7 2 9 is the next lowest power of 3 , and so f ( 9 5 5 ) = 9 5 5 + 7 2 9 = 1 6 8 4 .
Do you know how to show that this solution is unique?
Hint: Prove that
f
(
1
)
=
2
and
f
(
2
)
=
3
. Use condition 1 and 2.
Hence conclude that
f
(
3
n
)
=
2
×
3
n
and
f
(
2
×
3
n
)
=
3
×
3
n
. Use condition 2.
Hence, conclude that
f
(
n
)
has the formula that you described above. Use condition 1.
Log in to reply
Yes, that's basically how I came up with the function in the first place, by writing down f ( 1 ) through f ( 1 8 ) or so. That outline is quite elegant.
In my solution, I have used a notation, [a,b]->[c,d]. It means that for a<=x<=b, c<=f(x)<=d. If f(1)=n, f(f(1))=f(n)=3. Then f(f(n))=f(3)=3n. Note if n=1, we have f(f(1))=3=f(1)=1(not possible), and for n>2, 4<=f(2)<=8, but in that case we won't have a fixed value of f(x) for some bigger values of x. Thus we conclude n=2. Then in the last interval [730,1457]->[1459,2186], we note that 1457-730=2186-1459=727, it means that no elements in domain and domain set are equal, hence the mapping of f in that interval will be linear, thus f(955)=955+727=1684
Problem Loading...
Note Loading...
Set Loading...
A bit of playing around identifies the pattern for this function, and then it is possible to prove by induction that f ( 3 n + j ) = 2 × 3 n + j f ( 2 × 3 n + j ) = 3 n + 1 + 3 j for 1 ≤ j ≤ 3 n and n ≥ 0 . Since 9 5 5 = 3 6 + 2 2 6 , we have f ( 9 5 5 ) = 2 × 3 6 + 2 2 6 = 1 6 8 4 .